2020
DOI: 10.1002/acr.24398
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Adverse Patient‐Reported Outcomes in Systemic Lupus Erythematosus: Results From a Prospective Longitudinal Cohort

Abstract: Objective. Health-related quality of life (HRQoL) is reduced in systemic lupus erythematosus (SLE), partly driven by comorbid depression. Among patients with SLE, the association between major depression and HRQoL, measured using the NIH's Patient-Reported Outcomes Measurement Information System (PROMIS), is not well characterized. The objective was to determine an association between major depression and HRQoL as measured by PROMIS. Methods. Cross-sectional data were obtained from the California Lupus Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Higher prevalence of major depression was found among Egyptian SLE (64%) which was related to disease activity, not to steroids or duration of illness [43]. Depression worsens fatigue, discomfort, and psychological distress in SLE patients, as well as lowering adherence to drugs, resulting in a considerable reduction in quality of life [44].…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence of major depression was found among Egyptian SLE (64%) which was related to disease activity, not to steroids or duration of illness [43]. Depression worsens fatigue, discomfort, and psychological distress in SLE patients, as well as lowering adherence to drugs, resulting in a considerable reduction in quality of life [44].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a link between major depression in SLE and lower HRQoL [20]. However, details of the relationship, in particular the effects of depression on domains of the HRQoL are not well understood [21]. The present study aimed to determine the impact of major depression on the quality of life of SLE-relevant health domains and to evaluate other possible risk factors that can affect the quality of life.…”
Section: Introductionmentioning
confidence: 95%
“…[ 6 ] Depression in SLE has been directly associated with medication non-adherence, resulting in objective measures of increased disease activity as well as worse patient reported outcomes in multiple domains. [ 3 , 7 ]…”
Section: Introductionmentioning
confidence: 99%